Growth of Individual House Builders (IHB) in Raigad Districts - Sohil Shah (International Journal of Rural and Regional Development, 2024)
The study delves into the dynamic landscape of individual house builders (IHBs) in Raigad district, exploring the substantial growth within the real estate industry and its related sectors. The emphasis is on residential structures, ranging from bungalows to row houses and small individual buildings, designed to accommodate diverse family structures. This surge in construction activities is attributed to factors such as the abundant availability of land, improved connectivity, burgeoning employment opportunities, urbanization trends, and the expanding middle class. The construction of these dwellings is executed through various approaches, involving professional builders, contractors, self-development, or outsourcing. Raigad district, in particular, has witnessed exceptional progress in this domain, establishing itself as a fertile ground for individual house builders. The interplay of favorable circumstances, including land accessibility and increased connectivity, has spurred a remarkable increase in residential construction. The study adopts a descriptive analysis methodology to achieve its objectives. By scrutinizing the challenges encountered by individual home builders (IHBs) in Raigad district, the research aims to provide a comprehensive understanding of the obstacles that may hinder the growth of this sector. Simultaneously, it explores the growth trajectory of IHBs in the region, shedding light on the factors contributing to their success. The significance of this study extends beyond the immediate context, offering valuable insights into the potential of the real estate industry in Raigad district. The focus on a niche market allows for a nuanced exploration of the intricacies involved, providing stakeholders, policymakers, and industry players with a robust foundation for informed decision-making. As urbanization and economic development continue to shape Raigad district, this study stands as a timely and relevant exploration of the evolving dynamics within the local real estate landscape.
Keywords: Individual House Builders (IHB’s); construction; real estate